Self-recognition: a constraint on the formation of electrical coupling in neurons - Guthrie, PB (J Neurosci, 1994)
Electrical coupling between specific neurons is important for proper function of many neuronal circuits. Identified cultured neurons from the snail Helisoma show a strong correlation between electrical coupling and presence of gap junction plaques in freeze-fracture replicas. Gap junction plaques, however, were never seen between overlapping neurites from a single neuron, even though those same neurites formed gap junctions with neurites from another essentially identical identified neuron. This observation suggests that a form of self-recognition inhibits reflexive gap junction formation between sibling neurites. When one or both of those growth cones had been physically isolated from the neuronal cell body, both electrical coupling and gap junction plaques, between growth cones from the same neuron, were observed to form rapidly (within 30 min). Thus, inhibition of electrical coupling between sibling neurites apparently depends on cytoplasmic continuity between neurites, and not the molecular composition of neurite membrane. The formation of gap junctions is not likely due to the isolation process; rather, the physical isolation appears to release an inhibition of reflexive gap junction formation. These data demonstrate the existence of a previously unknown constraint on the formation of electrical synapses.